Об использовании рефлекса местоимения *tъ в функции определеннoго артикля в древяно-полабском - Супрун, Адам Евгеньевич (Kalbotyra, 1997)
In Dravaenopolabian reflexes of the pronoun *tъ sometimes were used as the function of the definite article. Parallels to such usage can be found in Serbo-Lusatian, Kаshubian and Slovenian. 15 examples of pronouns of this kind are presented in Dravaenopolabian texts. The German influence is the most probable cause of their usage, although the role of Slavic and European factors can not to be excluded. The obligatory and regularity of usage of the articles in Dravaenopolabian were not formed. Thus the articles were not still grammaticalizied.